Membentuk Akhlaqul Karimah pada Anak dalam Perspektif Pendidikan Islam - M. Abdillah Subhin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
Early age is the most basic period of growth and development of human life. In early childhood, all the potential of the child develops very quickly. Islam pays great attention to the issue of children's education, the concept of the formation of the noble ahlaq which is based on al-qur'an and hadith in order to always maintain a high courtesy and praiseworthy qualities that are expected to educate the Muslim generation, train and rectify his behavior, And directing it to words, deeds and properties of high value. Therefore education does not merely transfer knowledge to learners, but also provides moral values and humanitarian values that are general, and expected learners can respect others to be able to appreciate the lives of others, so that will be reflected in the behavior of polite, Humble, noble soul and self-confidence from early age to the end of life.